2017
DOI: 10.1007/s10639-017-9594-1
|View full text |Cite
|
Sign up to set email alerts
|

“Simply the best”: Professors nominated by students for their exemplary technology practices in teaching

Abstract: Our goal was to explore the technology related pedagogical practices of college professors deemed by their students to be excellent in using technology in their teaching. We explored the views of 114 community / junior college professors who were nominated by their students as excellent in using technology in their teaching using both questionnaires and interview methods. Results were analyzed using descriptive and inferential statistics. Results show no gender or years teaching in college differences in profe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 24 publications
(29 reference statements)
1
11
0
1
Order By: Relevance
“…It is possible that students can feel that they are expert because they use more social media and other non-academic ICTs. But this expertise may not transfer to academic ICTs, and professors may need to teach students how to use the ICTs needed for the course (Jorgensen, et al, 2018). Nevertheless students are not homogeneous in their level of ability, so it may be helpful if professors were to add Google references or YouTube videos to show students how to use required software.…”
Section: Proficiency In the Use Of Technologymentioning
confidence: 99%
See 2 more Smart Citations
“…It is possible that students can feel that they are expert because they use more social media and other non-academic ICTs. But this expertise may not transfer to academic ICTs, and professors may need to teach students how to use the ICTs needed for the course (Jorgensen, et al, 2018). Nevertheless students are not homogeneous in their level of ability, so it may be helpful if professors were to add Google references or YouTube videos to show students how to use required software.…”
Section: Proficiency In the Use Of Technologymentioning
confidence: 99%
“…This consists of a study which only examined students' experiences with the use of ICTs in post-secondary education (Fichten, et al, 2015) and a study which examined professors' perspectives (Jorgensen et al, 2018). Here we use a comparative framework to compare and contrast professor and student views.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…This research aligns with the interviews undertaken by Jorgensen et al (2018), which looked at the use of technology in pedagogy when teachers feel that their students are highly competent in the use of technologies. Their findings showed no variation between competence and willingness to employ technology between male and female teachers.…”
Section: Motivations For Adopting Instructional Technologysupporting
confidence: 76%
“…These outcomes replicate those of other studies that have found that educator technology training is most effective when it focuses on the use of the technology within the educational context and when the faculty members involved are trained in small groups. Jorgensen et al (2018) examined the technology-related pedagogical approaches that were employed by instructors who were of the perception that their students were excellent at using technology. The results revealed that male and female professors reported equal aptitude and comfort in the use of technology.…”
Section: A Multidisciplinary Group At Butler University Collaborated mentioning
confidence: 99%